The Impact of Digital Marketing on Consumer Purchase Decisions in Kathmandu Valley - Balampaki, Prajita; Rawat, Ramesh (Nepalese Journal of Management, 2025)
This study examines the impact of digital marketing on consumer purchase decisions in Kathmandu valley. Consumer purchase decision is selected as the dependent variable. Similarly, online advertising, email marketing, social media marketing, mobile marketing and brand awareness are selected as independent variables. This study is based on primary data with 120 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing impact on consumer purchase decision in Kathmandu valley. The study showed that online advertising has a positive impact on consumer purchase decisions. It means that better online ads lead to an increase in consumer purchase decisions. Similarly, email marketing has a positive impact on consumer purchase decisions. It indicates that an increase in email marketing leads to an increase in consumer purchase decisions. Moreover, social media marketing has a positive impact on consumer purchase decisions. It means that an increase in social media marketing leads to an increase in consumer purchase decisions. Likewise, mobile marketing has a positive impact on consumer purchase decisions. It shows that the increase in mobile marketing leads to an increase in consumer purchase decisions. Further, brand awareness has a positive impact on consumer purchase decisions. It shows that an increase in brand awareness leads to an increment in consumer purchase decisions.